BARKOD DNA PADA TANAMAN GAMBIR (Uncaria gambir(Hunter) Roxb.) BERDASARKAN GEN matK DAN rbcL - Wardi, Epi Supri; Jamsari, Jamsari; Irwandi, Irwandi; Sartika, Diza; Ningsih, Azma Risilvia (Jurnal Ilmiah As-Syifaa, 2020)
Gambir (Uncaria gambir (Hunter) Roxb.) is a superior commodity of West Sumatra that has many benefits and has been used as a drug. Plant identification carried out morphologically has many weaknesses, with the development of electronic and genetic technology now a new method of species identification has been developed. plants and animals, namely DNA barcoding technology that uses standard short pieces of DNA Species identification methods have been agreed to using standard DNA barcodes are rbcL genes and matK genes. The purpose of this study is to find out DNA Barkoding candidates between matK and rbcL which can identify gambier (Uncaria gambir (Hunter) Roxb.) Which is good. Polymerase Chain Reaction (PCR) technique is used to amplify rbcL and matK gene sequences through universal primers. The DNA sequences of the MATC sequence in the GR sample (Riau Gambir) produced a similarity rate of 98.79% with Nauclea diderrichii, for the rbcL sequence GC (Cubadak Gambir) samples produced a similarity rate of 99.81% with Uncaria macrophylla, and GR (Gambir Riau) samples produced the similarity rate was 96.84% with Uncaria macrophylla based on analysis with BOLD Systems. This similarity indicates the low variation in intraspecific genetics for the identification or confirmation of gambir species